IMBEDS: serviço inteligente para gerenciamento de leitos, utilizando ciência de situação - Grübler, Murillo da Silveira (Universidade do Vale do Rio dos Sinos, 2016)
The Bed Management is an important area of planning and control hospital. It’s function is to ensure the balance between the patients who come through the emergency department, elective that have some scheduled treatment and those leaving the hospital. Thus, the Bed Management enables the hospital keep high occupancy rate of rooms, but without fill all the beds, in addition to providing any unplanned situation. Effective management of hospital beds as a resource has always been a challenge for managers. In the 80s and 90s, for example, thousands of patients have operations canceled due to non-medical reasons. As there is need for better control of the flow, Bed Management area then began to receive more academic attention and also policies national for the Bed Management. The process of admission and positioning the patients, from the management of beds, has been developing in recent years through of operational research, such as simulation, queuing theory, statistical analysis, among others. Due to the uncertainties experienced by hospitals nowadays, the use of model Situation Awareness in research in the health field is growing increasingly. Situation Awareness is a field of study that seeks to understand the context of the environment and designing future actions. In short, it is a technique that goes beyond the traditional information processing, as it seeks to explain human behavior in the operation of complex systems. In this statement, this work aims to use the Situation Awareness in Bed Management area, using a hybrid model that combines the technique Artificial Neural Network Multilayer Perceptron with the Multi-Attribute Value Theory for decision making, assisting managers in process of patient's allocation to the bed suitable in his treatment. Through the implementation of a prototype based on this hybrid model of decision support, named of IMBEDS, were evaluated 50 patients in a total of 266 beds managed by Beds Center, in the Hospital Mãe de Deus, located in Porto Alegre. The final result of the tests was 93.5% similarity between the bed apt selected by the model and the allocation process of the patients.
Keywords: Gerenciamento de leitos; Ciência de situação; Admissão de pacientes; Rede neural artificial; Teoria do valor multiatributo; Informática médica; Bed management; Situation awareness; Patient admission; Artificial neural network; Multi-attribute value theory; Medical informatics; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação